APAKAH ANDA BENAR-BENAR MENGENALI PESAING ANDA? - Setiadi Umar (Bina Ekonomi, 2005)
Paying attention  to competitor is as important as caring your  customers.  By giving full attention ONLY  to customers  and not aware of what your competitors  doing will create a very  fragile  condition. Since, as we know, what we called  satisfaction, expectation, and customer value  is very  relative to competitors offering. Their values are not absolute.  There are many companies who have  lack  information about their competitor. Many do not even know, whether they have competitor or not. It is because  they are the only one of their kind or because  they are market  nicher. According to Levitt, these enterprises are suffering what he called marketing myopia. Actually (in the real situation) they do have  competitor  in the greater context. Even though  their products are not similar,  however  they do serve similar  need.